2018
DOI: 10.1557/mrc.2018.94
|View full text |Cite
|
Sign up to set email alerts
|

On the identification of Sb2Se3 using Raman scattering

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 31 publications
11
45
0
Order By: Relevance
“…Raman spectroscopy is capable of revealing the chemical states of the Sb 2 Se 3 absorber originally protected by TiO 2 layer. [42] We believe that this broad feature represents the decomposed products from the surface of Sb 2 Se 3 , which are either Sb 2 O 3 or Se, as described in Equation (2 The most intense peak (A 2g ) at ≈190 cm −1 along with a sub-peak at ≈210 cm −1 clearly confirms the presence of the Sb 2 Se 3 phase, which matches well with the previous reports on Raman studies of Sb 2 Se 3 .…”
Section: Resultssupporting
confidence: 89%
“…Raman spectroscopy is capable of revealing the chemical states of the Sb 2 Se 3 absorber originally protected by TiO 2 layer. [42] We believe that this broad feature represents the decomposed products from the surface of Sb 2 Se 3 , which are either Sb 2 O 3 or Se, as described in Equation (2 The most intense peak (A 2g ) at ≈190 cm −1 along with a sub-peak at ≈210 cm −1 clearly confirms the presence of the Sb 2 Se 3 phase, which matches well with the previous reports on Raman studies of Sb 2 Se 3 .…”
Section: Resultssupporting
confidence: 89%
“…The crystallized form of Sb 2 Se 3 gives rise to three A g ‐symmetry peaks at 117, 190, and 211 cm −1 and two B x g peaks at 150 and 153 cm −1 , all corresponding to Sb 2 Se 3. [ 52,56,57 ] Both materials crystallize in an orthorhombic structure, which is validated from the Raman modes.…”
Section: Resultsmentioning
confidence: 81%
“…No degradation effects (peak at 250 cm À1 or higher) were observed in any of the spectra acquired. The power density at which oxidation occurs varies across studies 11,15 and was observed to vary even for different crystal planes. Analysis of this behaviour requires further work and is beyond the scope of this study but may be dependent on the wavelength of the illuminating laser and/or surface termination of the sample.…”
Section: Experimental and Computational Detailsmentioning
confidence: 98%
“…Raman spectroscopy is a fast and usually non-destructive technique which can be used to characterise Sb 2 Se 3 and its impurity phases. 11 While gaps in the literature remain, some recent analysis of Sb 2 Se 3 via Raman spectroscopy has furthered the current understanding of this material. In 2018, Shongalova et al resolved an issue of misinterpretation of one of the peaks in the analysis of previous Raman spectra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation